Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - IX (Coleoptera, Cicindelidae). - Döbler, Helga (Contributions to Entomology = Beiträge zur Entomologie, 1973)
A catalogue of the types of Cicindelida preserved in the collections oft the former Deutsches Entomologisches Institut is presented.